3D pose estimation and tracking in handball actions using a monocular camera - Šajina, R.; Ivašic-Kos, M. (Journal of Imaging, 2022)
Player pose estimation is particularly important for sports because it provides more accurate monitoring of athlete movements and performance, recognition of player actions, analysis of techniques, and evaluation of action execution accuracy. All of these tasks are extremely demanding and challenging in sports that involve rapid movements of athletes with inconsistent speed and position changes, at varying distances from the camera with frequent occlusions, especially in team sports when there are more players on the field. A prerequisite for recognizing the player`s actions on the video footage and comparing their poses during the execution of an action is the detection of the player`s pose in each element of an action or technique. First, a 2D pose of the player is determined in each video frame, and converted into a 3D pose, then using the tracking method all the player poses are grouped into a sequence to construct a series of elements of a particular action. Considering that action recognition and comparison depend significantly on the accuracy of the methods used to estimate and track player pose in real-world conditions, the paper provides an overview and analysis of the methods that can be used for player pose estimation and tracking using a monocular camera, along with evaluation metrics on the example of handball scenarios. We have evaluated the applicability and robustness of 12 selected 2-stage deep learning methods for 3D pose estimation on a public and a custom dataset of handball jump shots for which they have not been trained and where never-before-seen poses may occur. Furthermore, this paper proposes methods for retargeting and smoothing the 3D sequence of poses that have experimentally shown a performance improvement for all tested models. Additionally, we evaluated the applicability and robustness of five state-of-the-art tracking methods on a public and a custom dataset of a handball training recorded with a monocular camera. The paper ends with a discussion apostrophizing the shortcomings of the pose estimation and tracking methods, reflected in the problems of locating key skeletal points and generating poses that do not follow possible human structures, which consequently reduces the overall accuracy of action recognition.